2009
DOI: 10.1167/iovs.08-2322
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Posterior Capsular Opacification through Aldose Reductase Inhibition

Abstract: Purpose The purpose of this study was to evaluate the effect of aldose reductase (AR) inhibition on Posterior capsular opacification (PCO) using pig eye capsular bag model. Methods Pig eye capsular bags were prepared by capsulorhexis and cultured in medium without or with AR inhibitors for 7 days. Immunostaining was performed in paraformaldehyde-fixed capsular bags to determine the expression of proliferating cell nuclear antigen (PCNA), α-smooth muscle actin (SMA), β-crystallin, and intercellular adhesion m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 38 publications
1
34
0
Order By: Relevance
“…Previous studies from our lab and those from Ramana and Srivastava have shown that AR inhibition attenuates cell proliferation, cell migration and EMT process on LECs [9, 32]. In this study, we investigated different level of AR expression on primary LECs.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies from our lab and those from Ramana and Srivastava have shown that AR inhibition attenuates cell proliferation, cell migration and EMT process on LECs [9, 32]. In this study, we investigated different level of AR expression on primary LECs.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, aberration in integrin‐mediated cell anchoring has also been implicated in lens epithelial cell EMT (Mamuya et al ., 2014). Recent studies have also shown a role for aldose reductase, MMP, microRNA, and histone deacetylases in lens epithelial cell EMT (Yadav et al ., 2009; Wang et al ., 2013; Korol et al ., 2014; Xie et al ., 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies also implicate AR in the pathogenesis of uveitis [2527] and fibrotic changes associated with posterior capsular opacification [28, 29]. Genetic or pharmacological blockade of AR successfully alleviates inflammatory responses induced by endotoxin [25, 26, 3032] or hyperglycemia [3335].…”
Section: Introductionmentioning
confidence: 99%